(13x-7)-(21x-9)=

Simple and best practice solution for (13x-7)-(21x-9)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (13x-7)-(21x-9)= equation:


Simplifying
(13x + -7) + -1(21x + -9) = 0

Reorder the terms:
(-7 + 13x) + -1(21x + -9) = 0

Remove parenthesis around (-7 + 13x)
-7 + 13x + -1(21x + -9) = 0

Reorder the terms:
-7 + 13x + -1(-9 + 21x) = 0
-7 + 13x + (-9 * -1 + 21x * -1) = 0
-7 + 13x + (9 + -21x) = 0

Reorder the terms:
-7 + 9 + 13x + -21x = 0

Combine like terms: -7 + 9 = 2
2 + 13x + -21x = 0

Combine like terms: 13x + -21x = -8x
2 + -8x = 0

Solving
2 + -8x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2' to each side of the equation.
2 + -2 + -8x = 0 + -2

Combine like terms: 2 + -2 = 0
0 + -8x = 0 + -2
-8x = 0 + -2

Combine like terms: 0 + -2 = -2
-8x = -2

Divide each side by '-8'.
x = 0.25

Simplifying
x = 0.25

See similar equations:

| 36-(3x+4)=2(x+7)+x | | X+21=5x+29 | | 27+8.50x=78 | | 5=x+y+1 | | (8x+9)+(7x-11)= | | 21x-x^2-30=0 | | 10x-6x+204=10x+102 | | 1/4=1/2d | | (X+6)=144 | | 2x+x=-6-7x | | 2(x-4)+3=-15 | | N+6=5.5 | | 3v+2=14-v | | .35a-a=-1.3 | | 6p-8=2p+8 | | 11x+12=7x+40 | | 895-140x=1875 | | 2(x+9)=0 | | 2x^2-2x=64 | | 140x-895=1875 | | 6(x-9)=6 | | (3x-y)/(2x-Y)=1 | | (6x-3)+(9-7x)= | | 40-5(2x+10)=1 | | (3x-y)/(2x-y) | | 0.15t+2.50=6 | | 12.34+.08x=13.09-.11x | | -3+4k=5 | | 9m+32=6-4 | | 41+17.25x=24+21.50x | | -2x+3-5x-1=4x+5+x-1 | | 6(x+2)-(2x-3)= |

Equations solver categories